Siberian Fir Extract Used in Complex Therapy of Acute Respiratory Viral Infections - Valery Petrovich Sergun,; Evgenia Bereslavets,; Valentina Nikolaevna Burkova,; Valeriy Mikhailovich Poznyakovsky,; Elena Ragozinnikova,; Boisjoni Tokhiriyon, (International Journal of Medical Toxicology and Legal Medicine, 2024)
A new dietary supplement based on Siberian fir extract has been developed. The novelty of the product has been patented. The essence of the technology lies in the concentration of the extract under vacuum at a gentle temperature (40-50°C), which ensures maximum extraction of biologically active substances and stability of their functional properties. The dietary supplement was identified by the determination of α-bisabolol, borneol and α-terpineol alcohols, bornyl acetate and ketone esters. Phenolic compounds and maltol with antioxidant properties were identified. Evidence-based medical studies were conducted on the efficacy of the developed product by including it in the diet of patients with acute respiratory diseases. Clinical studies on the effectiveness of the product were conducted on a group of patients with acute respiratory viral infections (ARVI). The patients received the dietary supplement in addition to the basic therapy, three tablespoons every 4 hours until the symptoms were alleviated, then one tablespoon four times a day, 30 minutes before meals, dissolved in ¼ glass of water. The total duration of treatment was 10 days (for the main group). The comparison group consisted of 30 patients with similar manifestations of ARVI, who were prescribed only basic therapy in accordance with the current clinical recommendations of the Ministry of Health of the Russian Federation. The patient groups were compared by age (18-60 years), gender and concomitant disease. The duration of the main clinical symptoms in patients with ARVI and their proportion as well as serum interferon levels were analysed. The results of the studies showed the efficacy and safety of the tested form of the dietary supplement and its therapeutic potential in the complex therapy of patients with ARVI.